Work-family conflict and coping behaviour : a study of married nurses - Mat Said, Aini (1997)
The aim of the research was to examine the work-family conflict of married women nurses and analysed their coping strategies. It was hypothesised that shift work would heightened the intensity of work-family conflict. Data from 243 nurses were collected fro m one of the hospitals in Kuala Lumpur, using self administered questionnaire. Descriptive statistics and t-test analysis were utilised to analyse the data. Overall the nurses experienced low to moderate level of work-family conflict intensity. From the t-test analysis, it was found that there was no significant difference between the mean of the work-family conflict experienced by the nurses who worked on shift schedule and those who worked during normal hours.The most frequently adopted coping strategy was Type III (reactive role behaviour) strategy. This entails organising well and working hard to meet all the role demands expected of them. The next strategy which was regularly used in managing the work-family conflict was the Type II (personal role redefinition) which involves changing their own attitudes and perceptions of role expectations. Type I structural role redefinition which involves an active attempt to deal directly with role senders and lessen the conflict by mutual agreement on a new set of expectations was found to be the least popular coping strategy.